(untitled) (Nexo Revista Científica, 2022)
Wine and tourism are considered interrelated factors of regional winemaking and viticulture. Currently, due to the large supply of imported wines in the Russian retail trade, traditional Crimean wines have lost mass demand for the national consumer. The study object of the present article is the process of uncovering unique cultural and historical context through a game format using modern information technologies, namely, virtual reality and augmented reality. The study subject of the study is a set of participants in the Crimean viticulture and winemaking, namely, winegrowers, winemakers, tourism and logistics companies, hospitality enterprises, tourists, and vacationers at Russian resorts that are part of wine-growing regions or are located in reasonable proximity from a logistical viewpoint. The research subject is the relationship of these participants with the research object. The problem of low demand for traditional Russian wines in the national consumer market is solved through the employment of information and communication technologies, which are a kind of information technology.